2022
DOI: 10.1111/geb.13478
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season

Abstract: Aim: Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post-fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019-2020 fires.Location: Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…First, we note that the responses of individual species to fire and to fires of varying severity are related to ecological and life‐history characteristics of the species, and several studies have used frameworks of traits to evaluate the likely impacts of fires on plant species (Gallagher et al, 2022; Gallagher, Allen, et al, 2021; Gallagher, Butt, et al, 2021) and vertebrate species (Legge et al, 2021). Therefore, for invertebrate species with high fire overlap, we recommend the development and application of a trait database that can be used to evaluate species' relative susceptibility to fire, hence (when combined with fire overlap) to provide a more robust assessment of the likely impact of the fires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we note that the responses of individual species to fire and to fires of varying severity are related to ecological and life‐history characteristics of the species, and several studies have used frameworks of traits to evaluate the likely impacts of fires on plant species (Gallagher et al, 2022; Gallagher, Allen, et al, 2021; Gallagher, Butt, et al, 2021) and vertebrate species (Legge et al, 2021). Therefore, for invertebrate species with high fire overlap, we recommend the development and application of a trait database that can be used to evaluate species' relative susceptibility to fire, hence (when combined with fire overlap) to provide a more robust assessment of the likely impact of the fires.…”
Section: Discussionmentioning
confidence: 99%
“…For species with very high fire overlap, a large proportion of the population might have been killed and/or a large proportion of their habitat made unsuitable for surviving individuals and post-fire recovery, with responses to fire likely to vary among species. To date, such evidence has been documented mostly for vertebrates (Legge et al, 2021(Legge et al, , 2022Ward et al, 2020) and plants (Gallagher et al, 2022;Gallagher, Allen, et al, 2021). For example, Ward et al (2020) compared the fire extent with the distributions of all 1,511 Australian vertebrate taxa occurring in a 2.2 million km 2 study area (defined by the exceptional extent of the 2019-2020 wildfires; Figure 1) and reported that 70 of these vertebrate taxa (including 21 already listed as threatened) had ≥30% of their distributional extent burnt by these fires.…”
Section: Introductionmentioning
confidence: 99%
“…The papers in this special issue include vulnerability assessments of plant species (Gallagher et al, 2022), vertebrate fauna (Legge et al, 2022), squamates of conservation concern (including geckos, skinks and snakes, Santos et al, 2022), invertebrates (Marsh et al, 2022) and ecosystems (Keith et al, 2022). A common theme across these studies is that vulnerability assessments must consider fire response traits in combination with information on fire regimes, and not just the proportion of a species' range or ecosystem extent that was subject to fire.…”
Section: How Can We Rapidly Assess Fire Impacts To Improve Post‐fire ...mentioning
confidence: 99%
“…Further, such assessments must also consider whether species or ecosystems are exposed to other threatening processes, and their susceptibility to those threats. For example, Gallagher et al (2022) present a framework for post‐fire vulnerability assessments. The authors suggest that such assessments should identify: (a) potential mechanisms of species or ecosystem decline, (b) locations in the landscape where these mechanisms are most likely to have an impact, and (c) the species and ecosystems most susceptible to risks associated with these mechanisms.…”
Section: How Can We Rapidly Assess Fire Impacts To Improve Post‐fire ...mentioning
confidence: 99%
See 1 more Smart Citation